2020
DOI: 10.32014/2020.2518-170x.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrophysical Impact on the Physical and Chemical Characteristics of Coal Ash From the Maikuben Deposit

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The composition of the elements in the phosphate part of the feedstock, especially the fine phosphorite, cyclone and electrostatic precipitators formed during the production of agglomerate, as well as the IOR of different rocks of vermiculite and lignite are given in Table 2 [14]. 2 shows that the mixture contains microelements, which are necessary for plants, like sulfur, titanium, magnesium, potassium, carbon etc.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the elements in the phosphate part of the feedstock, especially the fine phosphorite, cyclone and electrostatic precipitators formed during the production of agglomerate, as well as the IOR of different rocks of vermiculite and lignite are given in Table 2 [14]. 2 shows that the mixture contains microelements, which are necessary for plants, like sulfur, titanium, magnesium, potassium, carbon etc.…”
Section: Introductionmentioning
confidence: 99%
“…Coal fines are located in necessary amounts at coal mines, at transhipment points and, very often, they can be placed in the useful areas, pose a significant threat of pollution of the nearest territory. Massive losses in coal mining lead to the search for additional types of work on the processing of coal fines [5][6][7][8][9] . Based on the description of the chemical composition and physical properties of coal, it can be concluded that existing methods for using coal do not allow to realize its raw material and energy potential fully.…”
Section: Introductionmentioning
confidence: 99%